Tbx5 variants disrupt Nav1.5 function differently in patients diagnosed with Brugada or Long QT Syndrome. Issue 4 (8th February 2021) - Nieto-Marín, Paloma; Tinaquero, David; Utrilla, Raquel G; Cebrián, Jorge; González-Guerra, Andrés; Crespo-García, Teresa; Cámara-Checa, Anabel; Rubio-Alarcón, Marcos; Dago, María; Alfayate, Silvia; Filgueiras-Rama, David; Peinado, Rafael; et al.
Abstract: Aims: The transcription factor Tbx5 controls cardiogenesis and drives Scn5a expression in mice. We have identified two variants in TBX5 encoding p . D111Y and p . F206L Tbx5, respectively, in two unrelated patients with structurally normal hearts diagnosed with long QT (LQTS) and Brugada (BrS) syndrome. Here, we characterized the consequences of each variant to unravel the underlying disease mechanisms. Methods and results: We combined clinical analysis with in vivo and in vitro electrophysiological and molecular techniques in human-induced pluripotent stem-cell-derived cardiomyocytes (hiPSC-CMs), HL-1 cells, and cardiomyocytes from mice trans -expressing human wild-type (WT) or mutant proteins. Tbx5 increased transcription of SCN5A encoding cardiac Nav1.5 channels, while repressing CAMK2D and SPTBN4 genes encoding Ca/calmodulin kinase IIδ (CaMKIIδ) and βIV -spectrin, respectively. These effects significantly increased Na current (INa ) in hiPSC-CMs and in cardiomyocytes from mice trans -expressing Tbx5. Consequently, action potential (AP) amplitudes increased and QRS interval narrowed in the mouse electrocardiogram. p. F206L Tbx5 bound to the SCN5A promoter failed to transactivate it, thus precluding the pro-transcriptional effect of WT Tbx5. Therefore, p. F206L markedly decreased INa in hiPSC-CM, HL-1 cells and mouse cardiomyocytes. The INa decrease in p. F206L trans -expressing mice translated into QRS widening and increased flecainide sensitivity. p. D111Y Tbx5 increased SCN5A expression but failed to repress CAMK2D and SPTBN4 . The increased CaMKIIδ and βIV -spectrin significantly augmented the late component of INa (INaL ) which, in turn, significantly prolonged AP duration in both hiPSC-CMs and mouse cardiomyocytes. Ranolazine, a selective INaL inhibitor, eliminated the QT and QTc intervals prolongation seen in p. D111Y trans -expressing mice. Conclusions: In addition to peak INa, Tbx5 critically regulates INaL and the duration of repolarization in human cardiomyocytes. Our original results suggest that TBX5 variants associate with and modulate the intensity of the electrical phenotype in LQTS and BrS patients. Graphical Abstract: